STRATEGI PENYUSUNAN PERANGKAT PEMBELAJARAN MATA PELAJARAN BAHASA INGGRIS MELALUI PETA KONSEP DALAM KURIKULUM MERDEKA - Susanto, Fajar; Rahmad Hidayat; Endang M. Rahayu; Hertiki; Armelia Nungki; Joesasono O. Soelistijowati; Claudia Fira Inne P (Universitas PGRI Adi Buana Surabaya, 2022)
The implementation of the Merdeka curriculum is a challenge for educators, especially for English teacher at the Vocational High School (SMK) level. This article describes strategies for preparing learning tools for Merdeka Curriculum 2022 for English Vocational High School subjects in the City of Surabaya for teachers who are the members of the English Subject Teacher Conference (MGMP) in the Surabaya area. The main goal is to provide material on how vocational school teachers should not only be able to understand the Merdeka Curriculum 2022 well, but also be able to create mind map English teaching and learning process. This article uses a qualitative descriptive method with the implementation method in the form of technical guidance. Data were obtained from observations during the implementation of training activities, technical guidance and mind map documents that were made and collected by teachers as participants. This training is also a medium for increasing the ability of 40 participating teachers in making learning tools. The teachers have shown success in making mind map and administration of learning tools properly according to their expertise and professionalism. However, in the future, improvements must be made continuously because the world of education is a world of endless learning.